The increasing of scientific writing skills through a heutagogy approach in Indonesian higher education - Hafizah Hafizah; Fara Diba Catur Putri; Apriyanti Widiansyah; Husna Farhana (Universitas Jambi, Magister Program of English Education Department, 2021)
The purpose of this study was to find out and understand (1) the process of improving scientific essay writing skills through a heutagogical approach to online learning and (2) the effectiveness of applying the heutagogical approach to improving students' scientific essay writing skills. The method used is action research. The research was conducted on students at a university in Jakarta, Indonesia. This research is participatory and collaborative and takes place in two cycles. Each cycle consists of planning, implementing, observing, and reflecting. Data were collected through writing tests and observations. The writing test results were assessed using the speech writing assessment guidelines. The results showed that applying the heutagogical approach in online learning could improve students' scientific essay writing skills. The mean score on the initial test was 67.88, with only 37.2% getting a score of 75. In the first cycle, the average value increased to 74.49 with a success percentage of 60.5, and in the second cycle, the average value increased to 78.95 with a success percentage of 81.4%. From the research results, it can be concluded that the heutagogical approach can improve students' scientific writing skills.